Physiological Responses of Robinia pseudoacacia and Quercus acutissima Seedlings to Repeated Drought-Rewatering Under Different Planting Methods - Liu, Xiao; Zhang, Qinyuan; Song, Meixia; Wang, Ning; Fan, Peixian; Wu, Pan; Cui, Kening; Zheng, Peiming; Du, Ning; Wang, Hui; Wang, Renqing (Frontiers in Plant Science, 2021)
Changing precipitation patterns have aggravated the existing uneven water distribution, leading to the alternation of drought and rewatering. Based on that variation, we studied species with different root form and water regulation strategy, Robinia pseudoacacia and Quercus acutissima, to determine physiological responses to repeated drought-rewatering under different planting methods. Growth, physiological, and hydraulic traits were measured using pure and mixed planting seedlings that were subjected to drought, repeated drought-rewatering (treatments), and well-irrigated seedlings (control). Drought had negative effects on plant functional traits, such as significantly decreased xylem water potential (Ψmd), net photosynthetic rate (AP), then height and basal diameter growth were slowed down, while plant species could form stress imprint and adopt compensatory mechanism after repeated drought-rewatering. Mixed planting of the two tree species prolonged desiccation time during drought, shown in that mixed planting slowed down Ψmd and AP decreasing, delayed desiccation time, and after rewatering, plant functional traits could recover faster than pure planting. Our results demonstrate that repeated drought-rewatering could make plant species form stress imprint, adopt compensatory mechanism, while mixed planting could weaken the inhibition of drought, and finally improve the overall drought resistance, this mechanism may provide a theoretical basis for afforestation and vegetation restoration in the warm temperate zone under rising uneven spatiotemporal water distribution.